Thank You to Our 2024 Reviewers - Alberto Montanari; Ana Barros; Thorsten Becker; Marc Bierkens; Sharon Billings; M. Bayani Cardenas; Eric Davidson; Nicolas Gruber; Eileen Hofmann; Mary Hudson; Tissa Illangasekare; Sarah Kang; et al. (AGU Advances)
Abstract The editorial team of AGU Advances is grateful for the excellent contributions of our peer reviewers. We rely on their expertise to ensure that the manuscripts submitted to the journal undergo a rigorous, fair, and timely review. Remarkably, during 2024, the journal benefitted from the dedication from 273 reviewers, contributing a total of 338 reviews. These reviewers represented 24 countries. These reviewers provided insights of tremendous and generous value, and they assisted our authors in strengthening the rigor, quality, and presentation of their scholarship. Peer reviewing provides a natural way to engage in continuous learning and professional development. The majority of our reviewers are geoscientists, although we also have interdisciplinary contributions as the scope of Advances covers the extended domain of geosciences, intersecting with economics, communication and computational science, and the social sciences at large. Authors benefit greatly from reviewers' comments and suggestions: already more than 10 years ago, a study reported that most authors (90%) believe that peer review improved the last paper they published (Mulligan et al., 2013, https://doi.org/10.1002/asi.22798). Although the research and publishing arena is rapidly changing, peer review is considered the optimal standard for evaluating and selecting quality scientific manuscripts for publication, and therefore is highly deserving of our appreciation. We thank all of our peer reviewers for their selfless service and dedication to the scientific community. Your continuing support to the authors and editorial team of AGU Advances is deeply appreciated.